Energy Saving and Carbon Neutrality in the Funeral Industry - Kuo-Hsien Lee; Chung-Chen Huang; Sophia Chuang; Cheng-Tsu Huang; Wen-Hsien Tsai; Chu-Lun Hsieh (Energies, 2022)
As a result of the global population growth since World War II, and the major impact of the COVID-19 pandemic on the increase in the number of deaths, carbon emissions resulting from cremations in the funeral industry have increased by more than initially expected. In order to achieve the goal of the Kyoto Protocol and the Paris Agreement, to reach net-zero carbon neutrality by 2050, in this study, we comprehensively examined the literature on the differences in burial methods in terms of carbon emissions, and undertook stepwise analysis of the solution’s sequence from 1990 to 2050 using the recurrence relations in the trend changes using 5-year intervals. By collecting the annual number of global deaths and calculating the average carbon emissions per death to be 245 kg, we analyzed and compared these data with the annual carbon dioxide amount and global population until 2050. In addition, the results for cremation and Cryomation were analyzed and compared to construct a model of comparative advantage. The results of this study show that Cryomation is more energy efficient and has a greater impact on carbon emission reduction than cremation because it does not require carbon emission elements such as embalming or coffins. Thus, Cryomation can effectively reduce damage to the environment. Taking appropriate strategies for the funeral industry to promote Cryomation can achieve the goals of environmental protection and sustainable development.